Prevalence and correlates of HIV, syphilis, and hepatitis B and C infection and harm reduction program use among male injecting drug users in Kabul, Afghanistan: A cross-sectional assessment - Rasuli M; Fiekert Katja; Stanekzai M; Nasir Abdul; Todd Catherine S; Vlahov David; Strathdee Steffanie A (BMC, 2011)
Abstract Background A nascent HIV epidemic and high prevalence of risky drug practices were detected among injecting drug users (IDUs) in Kabul, Afghanistan from 2005-2006. We assessed prevalence of HIV, hepatitis C virus (HCV), hepatitis B surface antigen (HBsAg), syphilis, and needle and syringe program (NSP) use among this population. Methods IDUs were recruited between June, 2007 and March, 2009 and completed questionnaires and rapid testing for HIV, HCV, HBsAg, and syphilis; positive samples received confirmatory testing. Logistic regression was used to identify correlates of HIV, HCV, and current NSP use. Results Of 483 participants, all were male and median age, age at first injection, and duration of injection were 28, 24, and 2.0 years, respectively. One-fifth (23.0%) had initiated injecting within the last year. Reported risky injecting practices included ever sharing needles/syringes (16.9%) or other injecting equipment (38.4%). Prevalence of HIV, HCV Ab, HBSAg, and syphilis was 2.1% (95% CI: 1.0-3.8), 36.1% (95% CI: 31.8-40.4), 4.6% (95% CI: 2.9-6.9), and 1.2% (95% CI: 0.5-2.7), respectively. HIV and HCV infection were both independently associated with sharing needles/syringes (AOR = 5.96, 95% CI: 1.58 - 22.38 and AOR = 2.33, 95% CI: 1.38 - 3.95, respectively). Approximately half (53.8%) of the participants were using NSP services at time of enrollment and 51.3% reported receiving syringes from NSPs in the last three months. Current NSP use was associated with initiating drug use with injecting (AOR = 2.58, 95% CI: 1.22 - 5.44), sharing injecting equipment in the last three months (AOR = 1.79, 95% CI: 1.16 - 2.77), prior incarceration (AOR = 1.57, 95% CI: 1.06 - 2.32), and greater daily frequency of injecting (AOR = 1.40 injections daily, 95% CI: 1.08 - 1.82). Conclusions HIV and HCV prevalence appear stable among Kabul IDUs, though the substantial number having recently initiated injecting raises concern that transmission risk may increase over time. Harm reduction programming appears to be reaching high-risk drug user populations; however, monitoring is warranted to determine efficacy of prevention programming in this dynamic environment.